PHYTOCHEMICAL STUDY OF THE ARIAL PARTS OF Cleome rutidosperma DC PLANT - S. M. Mizanur Rahman; Serajum Munira; M. Amzad Hossain (Indonesian Journal of Chemistry, 2008)
Two new compounds were identified as 2-ethyl-cyclohex-2-ene-6-hydroxy-methylene-1-carboxylic acid and 3b-hydroxy-lup-20(29)-en-28-oic acid, respectively, from the petroleum ether extracts of Cleome rutidosperma plant. These two constituents is the first time occurrence in this plant. The structures of the two different type of compounds are elucidated with the help of UV, IR, 1H-NMR, 13C-NMR, COSY, DEPT 90, DEPT 135 and mass spectral data.